Relationship Between Transaminase Enzyme Levels And Gamma GT In Diabetes Mellitus Patients With Diabetic Foot Ulcers: Hubungan Kadar Enzim Transaminase Dengan Gamma GT Pada Pasien Diabetes Mellitus Dengan Ulkus Kaki Diabetik - Emilia, Hilda; Aliviameita, Andika (Universitas Muhammadiyah Sidoarjo, 2021)
Diabetes Mellitus is a chronic disease when the body cannot use insulin or cannot produce insulin enough, and glucose level in the blood increases. Diabetic ulcers are open sores on the skin surface caused by complications of macroangiophaty which can lead to neurophaty and vascular insufficiency. This study aims to determine the relationship between transaminase enzyme levels and Gamma GT in diabetes mellitus patients with diabetic foot ulcers. The sample used in this study was 30 patients with diabetes mellitus with diabetic foot ulcers. Research samples were obtained at Rumah Luka Sidoarjo and examined in the Hematology Laboratory of the Faculty of Health Sciences Muhammadiyah University in March 2021. SGOT and SGPT examination used the UV Enzymatic method, while the Gamma GT examination used the Enzymatic colorimetric method. In the Correlation-Regression test, it was found that there was no significant relationship (p=0,481) between SGOT Gamma GT, but there was a significant relationship (p=0,037) between SGPT and Gamma GT. Conclusion there is a moderate correlation (r=0,413) between transaminase anzymes and gamma GT in diabetes mellitus patients with diabetic foot ulcers.